Effects of a combined method of normobaric hypoxia on the repeated sprint ability performance of a nine-time world champion triathlete: A case report - Gonzalez-Custodio, A.; Crespo, C.; Timón, R.; Olcina, G. (Behavioral Sciences, 2024)
Elite athletes are an under-represented population in scientific studies, and there are no works analysing the influence of hypoxia in elite triathletes. The aim of this study was to analyse the influence of different methods of normobaric hypoxia on repeated sprint ability (RSA) performance. This study was a case study with an elite triathlete who has won nine triathlon world championships. The study used a combination of different methods of normobaric hypoxia. The three methods combined were as follows: live high-train low interspersed; intermittent hypoxic training; and intermittent hypoxic exposure. This study analysed the influence of these methods on RSA performance in variables such as power output, saturation of muscular oxygen, heart rate and ventilatory variables (VO2 and VCO2). The triathlete was measured before the training protocol (PRE), just after (POST-D3) and 21 days after the end of the protocol (POST-D21). This type of protocol has shown that it can lead to an improvement in RSA performance in the number of sprints (PRE vs. POST-D3 vs. POST-D21: 19 vs. 24 vs. 28), power output (PRE 615 W vs. POST-D3 685 W vs. POST-D21 683W) and efficiency of the triathlete. This work may be useful in improving power output and repeated sprint ability for elite triathletes.